Simultaneous and Significant Improvements in Efficiency and Stability of Deep‐Blue Organic Light Emitting Diodes through Friedel‐Crafts Arylmethylation of a Fluorophore. Issue 5 (4th May 2020) - Feng, Quanyou; Tan, Kesheng; Zheng, Xiaojun; Xie, Songlin; Xue, Kai; Bo, Yifan; Zhang, He; Lin, Dongqing; Rao, Junfeng; Xie, Xinmiao; Xie, Linghai; Cao, Hongtao; et al.
Abstract: The front cover artwork is provided by the Huang Group at the Institute of Advanced Materials (IAM) at Nanjing University of Posts and Telecommunications (China). The image shows how comprehensive performances of deep‐blue organic light‐emitting diodes can be achieved through Friedel–Crafts arylmethylation of a fluorophore. Read the full text of the Communication at 10.1002/cptc.201900268 . Abstract : "A chemical strategy, namely Friedel–Crafts arylmethylation of a fluorophore, is employed to develop efficient and stable deep‐blue OLEDs. Upon Friedel–Crafts arylmethylation, significant improvements in electroluminescence efficiency and stability are simultaneously achieved for a DPFCz‐TRZ‐based deep‐blue OLED. The system exhibits outstanding comprehensive performances with a highest external quantum efficiency of 15.5 %, maximum brightness over 16000 cd m ‐2, long LT50 of 78 h at 500 cd m ‐2 and CIE coordinates of (0.15, 0.10)…" This and more about the story behind the front cover can be found in the Communication at 10.1002/cptc.201900268 .